Developing a Comprehensive Model of Motivation and Performance - Chung, Kae H. (Academy of Management Journal, 1968)
The comprehensive model of motivation and performance was expressed by the formula: P=a AblNb2Ib3Eb4, where A is ability, N needs, I incentives, and E expectancies. An empirical study, with a sample of 175 students, supported the predictability of performance of the model.